Impacts of climate change on shipping and business continuity management - Huang, Lulu. (2012)
Shipping business is important in facilitating commodity trade around the world. Its operation faces increasing risk of business interruptions from natural disaster. The recent disasters, namely the Thailand's Flood and Japanese tsunami, have caused destruction of infrastructure and operation. Climate change is a rising issue for discussion, its impact on shipping business will be researched in the project. Besides climate change, other causes to shipping business disruption are also within our concerns. The research aims to investigate and evaluate shipping industry’s current practices in managing disruptions and propose a set of holistic collaborative Business Continuity Management (BCM) guidelines for shipping companies and ports to ensure their business continuity.